Pengaruh Artificial Intelligence (ChatGPT) dan Motivasi Belajar terhadap Hasil Belajar Siswa Kelas 7 SMP Katolik Don Bosco Bitung - Kaunang, Sandra Stella Maris; Rompas , Parabelem Tinno Dolf; Daud , Metsi (Edutik : Jurnal Pendidikan Teknologi Informasi dan Komunikasi, 2025)
This study aims to determine the effect of the use of artificial intelligence (ChatGPT) and learning motivation on the learning outcomes of 7th grade students of Don Bosco Bitung Catholic Middle School. This study uses a quantitative approach with a correlational method. The sample consisted of 58 students who were selected randomly. The research instruments were in the form of a learning motivation questionnaire, an observation sheet for the use of ChatGPT, and documentation of learning outcome scores. The results of the analysis show that the use of ChatGPT and learning motivation have a significant effect on student learning outcomes. This finding indicates that the integration of technology and psychological factors can improve the quality of learning.